Model for simulation of photo-induced charges inside the hybrid LC cells. - Moszczyński, Paweł; Walczak, Andrzej; Marciniak, Piotr (Photonics Letters of Poland, 2013)
The mathematical model for quantitative description of the liquid crystal (LC) layer deformation inside an asymmetric hybrid liquid crystalline cell is presented. Asymmetry means that one aligning layer in the cell is composed as photoconductive polymer PVK:TNF while the second is covered with common aligning material (polyimide). The LC waveguide arises along laser beam path propagated in plane of LC layer (refraction of light is not presented). In presented model we proved that LC layer deformation is caused by synergy of electric fields: driving field, space charge field, and fields of the surface charge cumulated on facing borders PVK:TNF/ITO and PVK:TNF/LC. Full Text: PDF References A.Walczak, P.Moszczyński, E.Nowinowski-Kruszelnicki, Semiconductor–LC Layer Boundary and Photonic Structures, Molecular Crystals and Liquid Crystals, Volume 559, Issue 1,(2012), CrossRef A.Walczak, E.Nowinowski-Kruszelnicki, Waveguide couplers induced optically over organic junction, Opt. Eng. 47(3) (2008), CrossRef N. Kukhtarev, V. Markov, S. Odulov, M. Soskin, and V. Vinetskii, Holographic storage in electrooptic crystals, Ferroelectrics 22, 949 (1979), CrossRef N. Kukhtarev, T. Kukhtareva, A Unified Treatment of Radiation-Induced Photorefractive, Thermal, and Neutron Transmutation Gratings, Proceedings of the IEEE, Vol. 87, No. 11, p. 1857-1869, 1999, CrossRef J. S. Schildkraut, Yiping Cui, Zero-order and first order theory of the formation of space-charge gratings in photoconductive polymers, J. Appl. Phys. 72 (11), pp. 5055-5060, 1992, CrossRef J. S. Schildkraut, A. V. Buettner, Theory and simulation of the formation and erasure of space-charge gratings in photoconductive polymers, J. Appl. Phys. 72 (5), pp. 1888-1893, 1992, CrossRef W. D. Gill, Drift mobilities in amorphous charge-transfer complexes of trinitrofluorenone and poly-n-vinylcarbazole, J. Appl. Phys., Vol. 43, No. 12, pp. 5033-5039, 1972. CrossRef